Characterization of thermal-resistance in Ga2O3 Schottky barrier diodes with temperature-sensitive electrical parameters. (11th October 2021) - Li, Xuan; Feng, Shiwei; Feng, Zhihong; Lv, Yuanjie; Wang, Yuangang; He, Xin; Bai, Kun; Pan, Shijie
Abstract: The temperature and thermal resistance of Ga2 O3 Schottky barrier diodes were investigated using electrical methods with temperature-sensitive electrical parameters and the structure function method. The analysis was based on the voltage of the Schottky junction as a temperature-sensitive parameter so as to measure the junction temperature of Ga2 O3 Schottky barrier diodes. The junction-case thermal resistance of the Ga2 O3 Schottky barrier diodes was accurately extracted by the transient dual interface test method to be 39.04 °C W −1, which increased slightly with the increase of power current. In addition, the temperature extracted with the electrical method was compared with the result of infrared measurements, which indicated that the temperature extracted with the infrared was significantly higher than the result of the electrical method. This difference can be explained in that the temperature extracted by the electrical method was the temperature of the active region of the device, whereas the result of infrared presented the maximum temperature of the device. Furthermore, the low thermal conductivity of Ga2 O3 resulted in temperature inhomogeneity on the device surface and further increased the temperature difference. This study provides a convenient and non-destructive method for rapid measurement of the thermal characteristics of the Ga2 O3 Schottky barrier diodes, and enables rapid evaluation of the whole thermal system.